Dietary pattern characterisation among subfertile South Asian women and the impact of vitamin B12 intake on frozen embryo transfer outcomes: a cross-sectional study. Issue 1 (14th February 2021) - Ravichandran, Aravind; Babuji, Manimegalai; Gowri, Mahasampath; Karthikeyan, Muthukumar; Chandy, Achamma; Kunjummen, Aleyamma T; Kamath, Mohan S
Abstract: STUDY QUESTION: Is there a difference in dietary patterns among subfertile South Asian women undergoing frozen embryo transfer (FET)? SUMMARY ANSWER: Significant regional differences in dietary pattern exist among subfertile South Asian women undergoing FET. WHAT IS KNOWN ALREADY: Preconception consumption of certain food groups or adopting specific dietary patterns, such as the 'Mediterranean diet', and its level of adherence have been shown to enhance the odds of achieving a successful pregnancy in women undergoing ART. However, differences in geographic location, individual preference, cultural beliefs and local availability contribute to such dietary choices. There is also a predisposition to a vitamin B12 deficiency in those of South Asian ethnicity and a predominant pattern of vegetarian food intake. There is a paucity of studies analysing the type of dietary pattern followed by South Asian women, their vitamin B12 levels and the potential impact on ART treatment outcomes. STUDY DESIGN, SIZE, DURATION: This is a cross-sectional study of 159 South Asian women aged 21–37 years, belonging to the Eastern (n = 75) and Southern (n = 84) regions of India plus Bangladesh, and undergoing a FET cycle at a tertiary level infertility clinic between February 2019 and March 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women underwent dietary assessment using '24-hour dietary recall' to capture daily nutrient consumption. A 'Food Frequency Questionnaire' listing commonly consumed foods was used to record frequency of intake. The primary outcome was the characterisation of regional dietary patterns in the cohorts using principal component analysis (PCA). Secondary outcomes included association of vitamin B12 intake and serum levels with clinical and ongoing pregnancy. MAIN RESULTS AND THE ROLE OF CHANCE: Four components contributing to overall variance in dietary pattern were identified, namely: meat, poultry and seafood; green leafy vegetables and root tubers; fruits, dairy and sugar; nuts and oilseeds. PCA analysis showed a significantly higher consumption of two components in the East—meat, poultry and fish ( P < 0.001); green leafy vegetables and root tubers ( P < 0.001). All women reported taking preconception oral folic acid supplementation. The dietary intake of vitamin B12 and serum concentration correlated, showing a good validity of measured dietary intake ( r = 0.398; P ≤ 0.001). Compared to the Southern region, participants from the East showed a higher daily median intake of vitamin B12 (1.11 versus 0.28 mcg, respectively; P < 0.001) and a higher serum vitamin B12 levels (441 versus 239 pg/ml, respectively; P < 0.001). Ongoing pregnancy showed no association with dietary vitamin B12 intake (relative risk 0.90; 95% CI, 0.68 to 1.19) or serum vitamin B12 levels (relative risk 0.99; 95% CI, 0.73 to 1.33) after adjustments for female age, body mass index (BMI) and geographic differences. Women belonging to different quartiles of serum vitamin B12 concentration had a similar likelihood of ongoing pregnancy. LIMITATIONS, REASONS FOR CAUTION: Self-reported dietary assessment is prone to measurement errors owing to its subjective nature and recall bias. The study was not adequately powered to detect the impact of geographic differences in vitamin B12 intake and serum levels on FET treatment outcomes, the second objective. We adjusted for potential confounders, such as female age and BMI, but it is possible that residual confounders, such as physical activity, stress and use of dietary supplements, may have influenced the results. Extrapolation of the study findings to women undergoing ART in other populations should be made with caution. WIDER IMPLICATIONS OF THE FINDINGS: Our study findings suggest important differences in local dietary patterns within the South Asian region. Hence a personalised approach to dietary assessment and intervention when undergoing ART based on population dynamics is warranted. The geographic differences in the vitamin B12 intake or serum levels did not have an impact on the FET outcomes. There is also a need to further investigate the impact of such dietary differences on ART treatment outcomes in a large study population. STUDY FUNDING/COMPETING INTEREST(S): No grant from funding agencies in the public, commercial, or not-for-profit sectors was obtained. The authors have nothing to disclose. TRIAL REGISTRATION NUMBER: N/A